UPAYA MENINGKATKAN RASA NASIONALISME SISWA MELALUI LOMBA CERDAS CERMAT DI UPTD SDN 3 WAGIR - Syifa Aulia; Adisti Choiri Andani; Izzah Khaiurunnisaa; Zaytunil Hikma; Dede Indra Setiabudi (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
Efforts to increase, a sense of nationalism, a psyche where loyalty. someone who is totally devoted directly to the nation state on behalf of the entire nation. From Nationalism will flow a sense of social solidarity, a spirit of self-sacrifice and can foster a spirit of patriotism. The Quiz Competition is a learning technique through competitions, to be able to increase potential, talents, abilities, in thinking about general knowledge, as well as train thinking sharpness and dexterity in answering questions quickly and accurately. With this technique, students can measure their abilities by answering questions correctly and quickly. Generating students' interest in learning through a game approach is more effective in fostering curiosity and experience in playing smartly in an effective and motivating learning environment than not in the form of games. Nationalism is a deep understanding, loving the Nation and the state with a conscious sense of its citizens who jointly achieve to maintain, and devote the identity, integrity, prosperity, and strength of the Nation.